Sa-OR-S125-4 - Leader And Peer Ethical Behavior Influences On Job Embeddedness - Ferreira, A.I. (EAWOP 2017, 2017)
The literature shows that ethical leadership is positively correlated with proactive behaviors and employee effectiveness (Brown, Treviño and Harrison, 2005). However, the consequences of ethical leadership on employees’ outcomes are in the initial stages in terms of research (Hansen et al., 2013). Accordingly, the present study, through Hierarchical Linear Models techniques. examined the mediating and moderating contextual variables in the relationship between ethical leadership and job embeddedness using a sample of 277 employees from 40 different companies. Results revealed that ethical leadership is related to job embeddedness and that supervisor support mediated the influence of ethical leadership on job embeddedness. We also found that at the supervisory-level of analysis, peer unethical behavior moderated the indirect ethical leadership-job embeddedness relationship. In sum, we feel that this study has presented an important contribution to the literature on ethical leadership, as well as pertinent implications for management, considering our findings suggest that ethical leadership is related to job embeddedness, an important variable which explains various organizational outcomes (e.g., turnover, job satisfaction and productivity).